2019
DOI: 10.1111/ajad.12982
|View full text |Cite
|
Sign up to set email alerts
|

Physician and Pharmacist: Attitudes, Facilitators, and Barriers to Prescribing Naloxone for Home Rescue

Abstract: Background and ObjectivesWe implemented a naloxone education and distribution program in our academic health system. Despite the program, naloxone prescribing was not fully realized. This study aimed to identify the barriers to prescribing.MethodsWe conducted a prospective, cross‐sectional, mixed‐methods study of naloxone prescribers. Participants completed a questionnaire regarding their prescribing practices, attitudes, facilitators, and barriers to prescribing naloxone. Participants were then invited for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…A range of approaches are needed, including increasing support and expansion of opioid education and naloxone distribution programs, 26 enhancing pharmacist and prescriber education about naloxone, identifying and educating patients at elevated overdose risk, and addressing pharmacists' and providers' perceived barriers to distributing and prescribing naloxone. [27][28][29] Consistent with other studies, 15,21 we found higher rates of naloxone co-prescribing among patients prescribed long-term opioid therapy by pain/anesthesia doctors and nurse practitioners/physician assistants as well as higher rates in metropolitan counties. Interestingly, we also found naloxone co-prescribing rates followed an inverse U-pattern with respect to age, peaking with the 46-55 age group.…”
Section: Discussionsupporting
confidence: 91%
“…A range of approaches are needed, including increasing support and expansion of opioid education and naloxone distribution programs, 26 enhancing pharmacist and prescriber education about naloxone, identifying and educating patients at elevated overdose risk, and addressing pharmacists' and providers' perceived barriers to distributing and prescribing naloxone. [27][28][29] Consistent with other studies, 15,21 we found higher rates of naloxone co-prescribing among patients prescribed long-term opioid therapy by pain/anesthesia doctors and nurse practitioners/physician assistants as well as higher rates in metropolitan counties. Interestingly, we also found naloxone co-prescribing rates followed an inverse U-pattern with respect to age, peaking with the 46-55 age group.…”
Section: Discussionsupporting
confidence: 91%
“…Stigma was found to be a potential barrier to participation in naloxone programs [ 28 , 33 , 36 , 41 , 46 , 50 - 51 , 54 - 55 , 67 , 72 , 74 ]. When people who use opioids had not previously experienced an overdose, there was often denial that they would ever be at risk of overdosing and requiring naloxone treatment [ 67 ].…”
Section: Reviewmentioning
confidence: 99%
“…In addition, healthcare providers perceived that clients limited their interactions due to their fear of discrimination when accessing services [ 46 , 50 , 73 ]. Reviewing this literature revealed that there is a misconception among healthcare providers that distributing naloxone may promote continued or riskier opioid use [ 30 , 32 - 33 , 42 , 45 , 49 , 51 , 54 , 60 - 61 , 63 , 66 , 68 - 69 , 71 ]. Alternatively, healthcare providers perceived that naloxone distribution could pose a safety concern to the general public as a result of the potential aggressive behaviors associated with the naloxone recipient’s withdrawal side effects [ 24 , 33 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations